A Case of Trichinellosis in a 14-Year-Old Male Child at Hawassa University Comprehensive Specialized Hospital, Hawassa, Sidama, Ethiopia. (15th October 2021) - Melese, Abebe; Mohammed, Musa; Ketema, Worku; Toma, Alemayehu
Abstract : Background . Trichinellosis develops after ingestion of Trichinella cysts in pork meat. It is one of the most important parasitic human pathogens in the world. It is, however, underreported in part because none of the clinical manifestations are pathognomonic. The primary mode of transmission is ingestion of raw meat. Among the symptoms are muscle pain, swelling, and myopathy. High-grade fever and other systemic symptoms are not unusual. The hallmarks are ophthalmic and musculoskeletal manifestations, particularly conjunctival haemorrhage with periorbital edema and subungual splinter haemorrhage. Although the majority of infections are mild and asymptomatic, severe infections can result in enteritis, periorbital edema, and myositis. Presentation of the Case . A 14-year-old male patient from Oromia Region, Arsi Zone, West Arsi Zone, Bishan Guracha area, which is almost completely encircled by mountains, presented with a complaint of worsening easy fatigability and asymmetric right thigh enlargement lasting one month. The pertinent physical examinations on presentation were puffy face and eyes, and there was a 4 cm by 5 cm mass on the right lateral thigh with no overlying skin colour change, on-tender, and no discharge. Eosinophilia of 14% was noticed on the complete blood count. The definitive diagnosis of trichinellosis was made by muscle biopsy. He was then managed with albendazole and prednisolone and improved. Conclusion . Patients with periorbital edema, myositis, or eosinophilia should be evaluated for trichinellosis. Individuals who have these symptoms and a history of eating pork meat should be suspected of having trichinellosis. Before eating raw pork meat, it is recommended that it be cooked properly.